Key Influences on Students' Academic Success: Insights from Scholarly Research - Vitoria, Linda; Ramli, Marwan; Johar, Rahmah; Mawarpury, Marty (Journal of Educational Management and Learning, 2024)
Literature reveals that there are numerous factors that affect students' academic achievement. These factors range from internal factors with varying degrees of influence. Determining the dominant factors is highly useful as part of the effort and the planning of potential actions regarding what can be done to improve students’ academic achievement. The present study employed a systematic literature review method to identify the dominant factors. Results show that there are four dominant factors that affect students’ academic achievement. They are academic motivation, emotional intelligence, teachers, and peers. This finding confirms the complex nature of the factors that affect students’ academic achievement, which involve internal and external factors. Without disregarding the other factors, these findings suggest that schools and parents should pay close attention to the dominant factors in order to improve students’ achievement.